Perancanaan UI/UX Aplikasi pada Bengkel Mobil Tarno Berbasis Android dengan Menggunakan Metode Design Thinking - Wulan Julianti; M. Noviarsyah Dasaprawira; Lasimin Lasimin (Jurnal Teknologi Terpadu, 2025)
The Tarno Car Workshop is a four-wheeled vehicle repair service business located in Karangkemiri Village and has been operating for more than three years. However, in its operational activities, this workshop still relies on manual recording to manage customer data, service, scheduling, and repair history. Manual practice causes several problems, including inefficiencies in data management, delays in service, and potential recording errors. To overcome these problems, it is necessary to develop an Android-based Bengkelin application that aims to simplify the workshop service process. The design of this application uses the Design Thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test, that focus on understanding users' problems and needs and on creating effective solutions. The result is a simple application design with the main features of service scheduling, maintenance history recording, payment methods, and account management. The interface design is expected to support the smooth running of the service process and increase the operational efficiency of the Tarno Car Workshop.